Developing teachers' self-efficacy and adaptive teaching behaviour through lesson study. (March 2018) - Schipper, Tijmen; Goei, Sui Lin; de Vries, Siebrich; van Veen, Klaas
Highlights: Examining Lesson Study practices using a quasi-experimental mixed methods design. Significant group differences in terms of beliefs of efficacy in pupil engagement. Enhancing efficient classroom management and clarity of instruction. Promoting adaptive teaching through Lesson Study. Significant relationship between beliefs of self-efficacy and adaptive teaching. Abstract: Teachers are expected to address a broad range of diverse pupil needs but do not always feel capable or lack the skills to meet these high expectations. The professional development approach Lesson Study may address this. Therefore, this study examines whether participating in Lesson Study influences teachers' beliefs of self-efficacy and (adaptive) teaching behaviour. A quasi-experimental mixed methods design was used to compare pretest and posttest data of intervention and comparison group teachers ( N = 48). Significantly different results between the two groups arise in terms of efficacy in pupil engagement as well as classroom management and instructional behaviour. Immediate stimulated recall interviews provide insight in these outcomes and illustrate to what extent teachers addressed pupils' educational needs.